Expression Profiling of Plant Cell Wall-Degrading Enzyme Genes in Eucryptorrhynchus scrobiculatus Midgut - Gao, Peng; Liu, Zhenkai; Wen, Junbao (Frontiers in Physiology, 2020)
In China, the wood-boring weevil Eucryptorrhynchus scrobiculatus damages and eventually kills the tree of heaven Ailanthus altissima. To feed and digest the cell wall of A. altissima, E. scrobiculatus requires plant cell wall-degrading enzymes (PCWDEs).. In the present study, we used next-generation sequencing to analyze the midgut transcriptome of E. scrobiculatus. Using three midgut transcriptomes, we assembled 21,491 unigenes from 167,714,100 clean reads. We identified 25 putative PCWDEs, including 11 cellulases and 14 pectinases. We constructed phylogenetic trees with a maximum likelihood algorithm to elucidate the relationships between sequences of the PCWDE protein families and speculate the functions of the PCWDE genes in E. scrobiculatus. The expression patterns of 17 enzymes in the midgut transcriptome were analyzed in various tissues by quantitative real-time PCR (RT-qPCR). The relative expression levels of 12 genes in the midgut and two genes in the proboscis were significantly higher than those in the other tissues. The proboscis and midgut are the digestive organs of insects, and the high expression level indirectly indicates that these genes are related to digestion. The present study has enabled us to understand the types and numbers of the PCWDEs of E. scrobiculatus and will be helpful for research regarding other weevils’ PCWDEs in the future.